2021
DOI: 10.2147/cmar.s307873
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-Reactive Protein/Albumin Ratio is a Prognostic Indicator for Survival in Surgically Treated Gastrointestinal Stromal Tumors: A Retrospective Cohort Study

Abstract: Background: Systemic inflammation and malnutrition may promote tumor progression. C-reactive protein/albumin ratio (CAR) is linked to the poor long-term survival of several malignant tumors. Purpose: To explore the predictive value of CAR in gastrointestinal stromal tumors (GISTs). Methods: A retrospective study was conducted on 325 patients with primary GIST surgically treated with curative intent from 2009 to 2018. The cut-off point of CAR was set using X-tile software. Kaplan-Meier method and multivariate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Generally, in gastrointestinal cancer, increased CRP is associated with progressive disease, advanced stages of metastatic cancer, and poor survival [ 738 ]. Some case reports show notably elevated CRP values (>100 mg/L) during the diagnosis of extraintestinal Gastrointestinal Stromal Tumor (GIST), and a study indicated that CRP was higher while taking into account the location of the lower digestive tract, larger tumor size, and the higher mitotic index of the specific GIST [ 819 , 820 , 821 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…Generally, in gastrointestinal cancer, increased CRP is associated with progressive disease, advanced stages of metastatic cancer, and poor survival [ 738 ]. Some case reports show notably elevated CRP values (>100 mg/L) during the diagnosis of extraintestinal Gastrointestinal Stromal Tumor (GIST), and a study indicated that CRP was higher while taking into account the location of the lower digestive tract, larger tumor size, and the higher mitotic index of the specific GIST [ 819 , 820 , 821 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%